The effectiveness of augmented reality-based e-modules in improving computer system learning outcomes - Vivi Gesilanda; Nurkhamid Nurkhamid (Himpunan Pengembang Kurikulum Indonesia, 2025)
Conventional learning on computer systems material in informatics often makes students passive, making it difficult for them to understand abstract concepts and leading to suboptimal learning outcomes. This study aims to analyze the effect of applying the Problem-Based Learning (PBL) model, assisted by Augmented Reality (AR), on the informatics learning outcomes of Grade 10 students. The research method used was a quasi-experiment with a pretest-posttest control group design. The sample consisted of several students divided into two groups: an experimental class that received the PBL-AR treatment and a control class that used conventional learning. Learning outcome tests were used as instruments, and data were analyzed using the N-Gain test after passing normality tests. The results showed a significant difference. The average posttest score of the experimental class significantly exceeded that of the control class, despite both groups having relatively comparable pretest scores. N-Gain analysis confirmed that the experimental class achieved improvement within the 'moderately effective' category, whereas the control class only reached the 'ineffective' category. It was concluded that the PBL model assisted by AR is significantly more effective in improving student learning outcomes on computer systems material. This innovative approach successfully increased active engagement and understanding of abstract concepts through interactive visualizations, thereby motivating students in the learning process. Abstrak Pembelajaran konvensional pada materi sistem komputer informatika seringkali membuat murid pasif dan sulit memahami konsep abstrak, sehingga berdampak pada hasil belajar yang kurang optimal. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan model Problem Based Learning (PBL) berbantuan Augmented Reality (AR) terhadap hasil belajar informatika murid kelas X. Metode penelitian yang digunakan adalah kuasi-eksperimen dengan desain pretest-posttest control group. Sampel terdiri dari sejumlah murid yang dibagi menjadi dua kelompok: kelas eksperimen yang menerima perlakuan PBL-AR dan kelas kontrol yang menggunakan pembelajaran konvensional. Instrumen penelitian menggunakan tes hasil belajar, dan data dianalisis menggunakan uji N-Gain setelah lolos uji normalitas. Hasil penelitian menunjukkan perbedaan yang sangat signifikan. Rata-rata nilai posttest kelas eksperimen jauh melampaui kelas kontrol, setelah sebelumnya kedua kelompok memiliki nilai pretest yang relatif setara. Analisis N-Gain mengonfirmasi bahwa kelas eksperimen mencapai peningkatan dalam kategori cukup efektif, sedangkan kelas kontrol hanya mencapai kategori tidak efektif. Disimpulkan bahwa model PBL berbantuan AR secara signifikan lebih efektif meningkatkan hasil belajar murid pada materi sistem komputer. Pendekatan inovatif ini berhasil meningkatkan keterlibatan aktif dan pemahaman konsep abstrak melalui visualisasi interaktif, menjadikan murid lebih termotivasi dalam proses pembelajaran. Kata Kunci: AR; hasil belajar; realitas tertambah; sistem komputer